SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/116007-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development and Use of High Density Fracturing Fluid in Deep Water Gulf of Mexico Frac and Packs

Abstract: In the Gulf of Mexico, there has been an increase in the number of wells drilled to depths greater than 20,000 ft with bottomhole pressures exceeding 20,000 psi. These deeper wells present drilling and completion challenges to the industry. Two of these challenges include fracture stimulation for low permeability and frac and pack sand control for higher permeability. Because of the high fracture gradient and friction in the wellbore tubulars, a conventional 1.0 to 1.04 SG fracturing fluid would require surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…are not suitable as weighting materials. Bromate (potassium bromide, sodium bromide) is a good weighting material, the density of its saturated solution can reach more than 1.8 g/cm 3 , which can significantly increase the adjustable range of fracturing fluid density [4][5][6]. However, it is difficult to be widely used due to its high cost.…”
Section: Characterization Of the Weighting Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…are not suitable as weighting materials. Bromate (potassium bromide, sodium bromide) is a good weighting material, the density of its saturated solution can reach more than 1.8 g/cm 3 , which can significantly increase the adjustable range of fracturing fluid density [4][5][6]. However, it is difficult to be widely used due to its high cost.…”
Section: Characterization Of the Weighting Agentmentioning
confidence: 99%
“…Years of studies showed that the weighted fracturing fluid systems used worldwide mainly include the following: borate crosslinking system [6], carboxymethyl hydroxypropyl guar gum zirconium crosslinking system [7], viscoelastic surfactant system [8], and guar gum organoboron crosslinking system [9], etc. The main components of the weighting agents are metal salts, such as sodium chloride, potassium chloride, calcium chloride, potassium bromide, sodium bromide, sodium nitrate, potassium formate, sodium formate and the mixture of inorganic and organic salts [4].…”
Section: Introductionmentioning
confidence: 99%
“…Increased Brine and Fracture Fluid Density: During recent years, a number of developments have taken place with heavy brine based frac fluids for deep formation opportunities, particularly in the Gulf of Mexico (Rivas et al, 2008) and (Simms et al, 2008). Increased Brine and Fracture Fluid Density: During recent years, a number of developments have taken place with heavy brine based frac fluids for deep formation opportunities, particularly in the Gulf of Mexico (Rivas et al, 2008) and (Simms et al, 2008).…”
Section: Increased Bottomhole Pressurementioning
confidence: 99%
“…The operator already had experience with a weighted stimulation fluid system from previous projects and extensive laboratory work (Simms et al 2008, Rivas et al 2008. The operator already had experience with a weighted stimulation fluid system from previous projects and extensive laboratory work (Simms et al 2008, Rivas et al 2008.…”
Section: Stimulation Materials and Logisticsmentioning
confidence: 99%